Stable propagation of orbital angular momentum modes in pedestal waveguides - Borda-Hernández, Jos A.; Alayo, Marco I.; Carvalho, Daniel O. [UNESP]; Hernández-Figueroa, Hugo E. (Optica Publishing Group, 2018)
We use numerical simulations to show that, even under common perturbations such as waveguide bends, pedestal waveguides are suited for stable propagation of modes carrying orbital angular momentum (OAM) in integrated devices.